The definite article in the Spanish of Persian learners - Parvizi, Pardis (Círculo de Lingüística Aplicada a la Comunicación, 2014)
The definite article is one of the most complex theoretical issues of the Spanish language. In this study we present the results of our research on Persian learners seeking to discover the most common mistakes when using the definite article in Spanish as the second-language. In order to achieve this, errors have been classified into three types: grammatical, syntactic and semantic. At the same time, the differences in each case in relation to the Persian language will be explained and the reasons causing these difficulties will be identified. The purpose of this research is to help of educate particular aspects of the Spanish language to native Persian students, that has not been investigated so far.
Keywords: definite article; Spanish as a second language; Persian langue; applied linguistics.